Subjective Well Being Mahasiswa Penyandang Disabilitas - Sri Wahyuni; Ribut Wahyu Eryanti; Atok Miftachul Hudha (Jurnal Pendidikan Tambusai, 2023)
This research is a literature review that aims to investigate the subject of Subjective Well-Being in students with disabilities. Subjective well-being covers various aspects of life which include happiness, life satisfaction, and individual perceptions of the quality of their life. Students with disabilities face unique and varied challenges in achieving their subjective well-being, due to being in an academic environment that is often not fully aware of their needs. This literature research will explore scientific articles, journals, books, and other trusted sources that discuss the subjective well-being of students with disabilities. Research will evaluate the factors that affect their subjective well-being, including social support, accessibility of facilities, level of participation in academic and non-academic activities, and the role of self-perception in the adaptation process. In addition, this research will also identify the challenges and obstacles faced by students with disabilities in achieving their subjective well-being. Some of the possible challenges include social stigmatization, lack of awareness of their needs, as well as physical and psychological limitations that affect their participation in campus life. It is hoped that the results of this literature review can provide better insight on how to improve the subjective well-being of students with disabilities in the higher education environment. The practical implications of this research can help educational institutions to develop more inclusive policies and programs, as well as provide appropriate resources and support for students with disabilities. In addition, this research can also identify research areas that need more exploration in the future to better understand and improve the subjective well-being of this group.